2014
DOI: 10.1177/000313481408000910
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Repair of Duodenal Atresia in a Low Birth Weight Neonate

Abstract: The small volume of the infant abdomen limits the application of laparoscopic procedures. We successfully repaired a duodenal atresia in a 2-kg female infant using a standard diamond-shaped anastomosis and intracorporeal suturing and knot-tying techniques. Anesthesia and positive pressure ventilation assured adequate gas exchange during pneumoperitoneum during the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Twelve studies were initially identified [3–12, 15, 16] from 2002 to 2014, of which four were case reports [3, 4, 15, 16] and were excluded. Eight studies were included [5–12], of which five focused on LRDA ( n = 67 patients) [5–9], and three were comparative between LRDA ( n = 57 patients) and conventional open repair ( n = 94 patients) [10–12].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies were initially identified [3–12, 15, 16] from 2002 to 2014, of which four were case reports [3, 4, 15, 16] and were excluded. Eight studies were included [5–12], of which five focused on LRDA ( n = 67 patients) [5–9], and three were comparative between LRDA ( n = 57 patients) and conventional open repair ( n = 94 patients) [10–12].…”
Section: Resultsmentioning
confidence: 99%
“…In these patients, the entire small and large bowel are decompressed, allowing for excellent workspace even in low birth babies (according to our surgical experience with neonatal MIS approach) and there is an excellent exposure of the proximal duodenum. The laparoscope helps achieve a magnification of the operatory intra-abdominal field and consequently an accurate anastomosis even in bowel with a diameter of less than 5 mm [ 12 ]. The lack of distal bowel manipulation and probably the most declivous anastomosis seems to result in a shorter ileus and earlier initiation of feeds as described in a recent report by Spilde et al [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…This decision was made, because in Japan surgical outcome for premature babies weighing less than 2500 g at birth is still undesirable, although this has improved immensely for term babies of normal weight [ 15 ]. In case early surgical intervention is indicated in premature or low birth weight neonates, minimally invasive approaches are recommended for safety [ 16 , 17 ]. Recently, it has become possible to treat neonatal surgical diseases in an effective and safe way with the laparoscopic technique [ 11 , 18 ].…”
Section: Discussionmentioning
confidence: 99%